TELISIK TREND RISET MAQASHID SYARIAH DALAM KONTEKS BANK SYARIAH - Noviana Prasanti (Jurnal Bina Bangsa Ekonomika, 2024)
This research was conducted to examine research trends in sharia maqashid in sharia banks in Indonesia during the 2017-2022 period. This research uses qualitative research. The data collection technique used in this research is a literature review. The sample used in this research was determined using purposive sampling. The data analysis method used in this research is charting the field. Based on the research results, it can be concluded that, over a period of 5 years, research discussing research trends in sharia maqashid in sharia banking has increased every year. Apart from that, most research methods are dominated by quantitative research. And the type of research is descriptive with mostly using secondary data